A Comparison of Usability Factors of Four Mobile Devices for Accessing Healthcare Information by Adolescents - Sheehan, B.; Lee, Y.; Rodriguez, M.; Tiase, V.; Schnall, R. (Applied Clinical Informatics, 2012)
Background: Mobile health (mHealth) is a growing field aimed at developing mobile information and communication technologies for healthcare. Adolescents are known for their ubiquitous use of mobile technologies in everyday life. However, the use of mHealth tools among adolescents is not well described.Objective: We examined the usability of four commonly used mobile devices (an iPhone, an Android with touchscreen keyboard, an Android with built-in keyboard, and an iPad) for accessing healthcare information among a group of urban-dwelling adolescents.Methods: Guided by the FITT (Fit between Individuals, Task, and Technology) framework, a think-aloud protocol was combined with a questionnaire to describe usability on three dimensions: 1) task-technology fit; 2) individual-technology fit; and 3) individual-task fit.Results: For task-technology fit, we compared the efficiency, and effectiveness of each of the devices tested and found that the iPhone was the most usable had the fewest errors and prompts and had the lowest mean overall task time For individual-task fit, we compared efficiency and learnability measures by website tasks and found no statistically significant effect on tasks steps, task time and number of errors. Following our comparison of success rates by website tasks, we compared the difference between two mobile applications which were used for diet tracking and found statistically significant effect on tasks steps, task time and number of errors. For individual-technology fit, interface quality was significantly different across devices indicating that this is an important factor to be considered in developing future mobile devices.Conclusions: All of our users were able to complete all of the tasks, however the time needed to complete the tasks was significantly different by mobile device and mHealth application. Future design of mobile technology and mHealth applications should place particular importance on interface quality.Citation: Sheehan B, Lee Y, Rodriguez M, Tiase V, Schnall R. A Comparison of Usability Factors of Four Mobile Devices for Accessing Healthcare Information by Adolescents. Appl Clin Inf 2012; 3: 356–366http://dx.doi.org/10.4338/ACI-2012-06-RA-0021
Keywords: Adolescents; mobile health (mHealth); usability; health information